Smoking behavior is associated with suicidality in individuals with psychosis and bipolar disorder: a systematic quantitative review and meta-analysis - Pietschnig, Jakob; Oberleiter, Sandra; Köhler, Marcel D. (Frontiers in Psychology, 2024)
Smoking behavior has been well-established to be more prevalent in individuals with psychosis and bipolar disorder compared to the general population. However, reports about higher suicide attempt prevalence of smoking compared to non-smoking patients suggest that smoking behavior may contribute to identifying at-risk groups of patients in a comparatively easy manner. In the present systematic quantitative review, we provide meta-analytical evidence on the smoking and suicide attempt link in 22 studies (k = 27 independent samples; N = 11,452) of patients with psychosis and bipolar disorder. We observed a small meaningful effect of smoking on suicide attempts (OR = 1.70; 95% CI [1.48; 1.95]), indicating that smokers have 1.70 the odds of having reported a suicide attempt compared to non-smokers. This effect generalized across diagnosis type (i.e., schizophrenia vs. bipolar spectrum disorder), sample type (i.e., in-vs. outpatients), and participant sex. However, the observed summary effect appeared somewhat inflated due to publication process-related mechanisms, showing some evidence for effect-inflating publication bias and a decline effect. In all, the presently observed smoking and suicide attempt link appears to be small but meaningful and robust, thus suggesting smoking status represents a useful variable for the identification of at-risk populations for suicide attempts.